University students’ perceptions of multilingual education: A case study of the North-West University Mafikeng campus - Hlatshwayo, Abigail; Siziba, Liqhwa P. (Stellenbosch Papers in Linguistics Plus, 2014)
The dominant position of neo-liberal monolingual medium-of-instruction practices has created myths and fallacies about the utility of English as the sole language of skills development and training in South Africa (Ndhlovu 2013:33). As a result, most tertiary institutions are reluctant to implement multilingual education for purposes of teaching and learning because they want to create “globally relevant” students. This argument is based on myths and has been proven by many scholars to be delusive. Current research has proven that the use of multilingualism in higher learning contributes to the learner’s conceptual and pedagogical development as well as his/her communicative competence. However, despite this evidence, the North-West University’s (NWU) Mafikeng campus is failing to implement a language policy that promotes multilingualism. A commonly-heard argument is that the students at NWU have a negative attitude towards the use of their indigenous languages for teaching and learning purposes. It is in light of this that the researchers set out not only to interrogate the NWU language policy, but also to go a step further and investigate the students’ perceptions of multilingual education as a factor contributing towards the lack of practical implementation of the university’s language policy. This study will also highlight the ill-preparedness of students for an English-only teaching and learning environment. The tentative empirical data prove that the students also feel that they are at a linguistic disadvantage when entering the tertiary institution. This paper returns to the knotty question regarding language-in-education policies for multilingual societies, which is an ongoing topical issue in national and international contexts.